Spin caloric transport from density-functional theory - Popescu, Voicu; Kratzer, Peter; Entel, Peter; Heiliger, Christian; Czerner, Michael; Tauber, Katarina; Toepler, Franziska; Herschbach, Christian; Fedorov, Dmitry V.; Gradhand, Martin; Mertig, Ingrid; Kovacik, Roman; et al. (JOURNAL OF PHYSICS D-APPLIED PHYSICS, 2019)
Spin caloric transport refers to the coupling of heat with spin transport. Its applications primarily concern the generation of spin currents and control of magnetisation by temperature gradients for information technology, known by the synonym spin caloritronics. Within the framework of ab initio theory, new tools are being developed to provide an additional understanding of these phenomena in realistic materials, accounting for the complexity of the electronic structure without adjustable parameters. Here, we review this progress, summarising the principles of the density-functional-based approaches in the field and presenting a number of application highlights. Our discussion includes the three most frequently employed approaches to the problem, namely the Kubo, Boltzmann, and Landauer-Buttiker methods. These are show cased in specific examples that span, on the one hand, a wide range of materials, such as bulk metallic alloys, nano-structured metallic and tunnel junctions, or magnetic overlayers on heavy metals, and, on the other hand, a wide range of effects, such as the spin-Seebeck, magneto-Seebeck, and spin-Nernst effects, spin disorder, and the thermal spin-transfer and thermal spin-orbit torques.